Building a Successful Palestinian State - Gompert, David (RAND Corporation, 2005)
An examination of how an independent Palestinian state, if created, can be made successful. The authors describe options for strengthening governance, security, economic development, access to water, health and health care, and education, and estimate the financial resources needed for successful development over the first decade of independence.